Freudian Psychology: an Analysis on Catherine Barkley in Ernest Hemingway’s A Farewell to Arms - Yulistiyanti Yulistiyanti (Dinamika Bahasa dan Budaya, 2011)
A Farewell to Arms is one of Hemingway’s works which uses battle field as setting. This novel is full of humanism message which depict social problem people have. The social problem, war depicted causes personal problem for people represented by one of Hemingway’s character, Catherine Barkley. Sigmund Freud contributes to find out the personal problems which form ego self-defense mechanism. There are five ego self-defense mechanism; repression, projection, reaction-formation, fixation, and regression. The five ego self-defense mechanisms are found in this novel.   Key words: ego self-defense mechanism, repression, projection, reaction-formation, fixation, regression.